THE CRIMINAL LAW POLICY FORMULATION IN LAW NUMBER 22 OF 2009 CONCERNING TRAFFIC AND TRANSPORTATION - Kurnianingsih, Marisa (Tadulako Law Review, 2016)
Abstract This paper focuses on the criminal law formulation policy related to criminal Law No. 22 of 2009 concerning Traffic and transportation. The policy formulation certainly need to be tied in every stage of the making, the implementation and accomplishment in order to create a sustain system.Â  The formulation policy or the stage of making the law is a fundamental policy in criminal law policy because formulation policy is determinant of to whether a law could be applied in society. The issues discussed in this paper are: (1) How the formulation policy of criminal law in Law Number 22 Year 2009 regarding Traffic and transportation? (2) How the formulation policy of criminal law in the Law of Traffic and Transportation in the future? Firstly, the formulation policy of Law Number 22 Year 2009 regarding Traffic and Transportation will be discussed with three main discussion of criminal law which are criminal offense, criminal liability, and crime. Secondly, for the formulation policy of criminal law in the Law concerning traffic and transportation in the future the writer employs the concept of Penal Code 2012 as consideration to attain a formulation that could improve the current formulation. Such formulations are as followed:(a) qualifying offense should be retained but must be consistent with the legislators in the inclusion of criminal penalty so legal result will be clear. (b) In the arrangement of criminal penalty the criminal objective and guideline is needed. Keywords: policy formulation, criminal law, and Traffic